2019
DOI: 10.1039/c9cp00647h
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity and stability of plasma-generated oxygen and nitrogen species in buffered water solution: a computational study

Abstract: Plasma-treated liquids have great potential for biomedical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 45 publications
7
57
0
Order By: Relevance
“…This addresses one of the main reasons for the scepticism towards plasma medicine. Direct plasma treatment provides targeted delivery of highly short-lived RONS during treatment, while plasma-treated media generates persistent and semi-persistent molecular and ionic compounds, including e.g., H 2 O 2 , nitrous and peroxynitrous acid [13,55]. These compounds are commercially available, and their use technically does not require the employment of cold plasma.…”
Section: Identifying Optimal Parameters For Anti-cancer Treatmentsmentioning
confidence: 99%
“…This addresses one of the main reasons for the scepticism towards plasma medicine. Direct plasma treatment provides targeted delivery of highly short-lived RONS during treatment, while plasma-treated media generates persistent and semi-persistent molecular and ionic compounds, including e.g., H 2 O 2 , nitrous and peroxynitrous acid [13,55]. These compounds are commercially available, and their use technically does not require the employment of cold plasma.…”
Section: Identifying Optimal Parameters For Anti-cancer Treatmentsmentioning
confidence: 99%
“…The downward‐directed He jet can deform the surface of the liquid and induce circulation in the liquid . We have chosen a more simplified model with a nondeforming surface.…”
Section: Description Of the Modelmentioning
confidence: 99%
“…The downward-directed He jet can deform the surface of the liquid and induce circulation in the liquid. [40] We have chosen a more simplified model with a nondeforming surface. We expect that for the high-rimmed cases, there would be little effect on the gas flow patterns due to the curvature of the liquid as recirculation is dominated by the vertical walls.…”
Section: Description Of the Modelmentioning
confidence: 99%
“…It is understandable that non-cancerous cells normally require more advanced cell culture media with additional organic compounds compared to cancer cells, but the different media have disparate buffering and antioxidant capacities [31]. In fact, the stability of RONS in different liquids has been thoroughly investigated [32,33] and Yan et. al showed that the presence of cysteine and methionine can significantly degrade CAP-generated RONS [31].…”
Section: Introductionmentioning
confidence: 99%